Illuminating the process: Enhancing the impact of continuing professional education on practice. (February 2015) - Clark, Elisabeth; Draper, Jan; Rogers, Jill
Summary Background There has been significant global investment in continuing professional education (CPE) to ensure healthcare professionals have the knowledge and skills to respond effectively to the needs of patients/service users. However, there is little evidence to demonstrate that this investment has had a tangible impact on practice. Furthermore, the current emphasis on evaluating outcomes has overlooked the importance of underlying processes which, when positive, are essential to good outcomes. Objective The aim of this study was to identify the processes that key stakeholders perceive to be most important in facilitating a positive impact of CPE on practice. Design/method A qualitative design using two rounds of semi-structured interviews which were recorded and transcribed prior to analysis, informed by template analysis techniques. Setting Two acute trusts, one primary care trust and two higher education institutions in one geographical region in England. Participants Representatives from four stakeholder groups—students, managers, educators and members of each healthcare organisation's governing board. A total of 35 interviews were conducted in the first round and 31 interviews in the second round (n = 66). Results Four overarching themes were identified that illuminate stakeholders' perspectives of the important factors affecting the process of CPE: organisational structure, partnership working, a supportive learning environment and changing practice. Conclusions This study suggests that a positive organisational culture, effective partnership working between key stakeholders with an understanding of each other's perspectives, aspirations and constraints, and a supportive learning environment in both the practice setting and education environment are central to establishing a culture and context where CPE can thrive and exert a positive influence on improving patient/service user experience and care. It is argued that an understanding of the processes that facilitate effective CPE is a crucial first step before it is possible to meaningfully evaluate outcomes.